TEACHING STUDENTS NEW LEXICAL UNITS THROUGH MUSIC - Abdulxayev Farxodbek (Bright Mind Publishing, 2025)
The process of acquiring new lexical units in a foreign language is a crucial aspect of language learning, and various teaching methodologies have been developed to enhance students' vocabulary acquisition. Among these, the use of music as a pedagogical tool has gained increasing attention due to its effectiveness in facilitating memory retention, improving pronunciation, and creating an engaging learning environment. This article explores the role of music in teaching students’ new lexical units by examining the cognitive and emotional benefits of musical exposure, discussing various methodological approaches for integrating songs into language instruction, and analyzing the practical implications of using music to enhance vocabulary learning. Through a detailed examination of relevant studies and teaching experiences, this research highlights the advantages of utilizing music as a means of reinforcing lexical acquisition and provides practical recommendations for language educators. The findings suggest that music not only aids in long-term vocabulary retention but also enhances students' motivation and overall language proficiency.
Keywords: Lexical acquisition, foreign language teaching, music-based learning, vocabulary retention, phonological awareness, motivation in language learning, cognitive benefits of music.